Association of polymorphic G1934A variant (allele *4) of CYP2D6 gene with increased risk of breast cancer development in Ukrainian women - Levkovich, N.N.; Gorovenko, N.G.; Myasoedov, D.V. (Experimental Oncology, 2011)
Institute of Genetic and Regenerative Medicine of the Ukrainian Academy of Medical Sciences”, Kiev, 03150, UkraineBackground: Breast cancer (BC) is among the most common oncologic pathology in economically developed countries where it afflicts nearly 10% of women. Polymorphism of CYP 2D6 gene is shown to be associated with increased risk of development of a number of pathologies, in particular cancer. Aim: The work was directed on evaluation of the role of polymorphism G1934A (allele *4) of CYP 2D6 gene in elevated risk of BC development in Ukrainian women. Materials and Methods: In the study there were enrolled 85 patients (group І) with histologically verified BC diagnosis of stages I and ІІ. Clinical-genealogic study has been performed by the method of patient survey and following analysis of genealogy. Earlier obtained data on the frequency of genotypes and alleles of CYP 2D6 gene in 637 Ukrainian people have been used as a control. For determination of allele variant *4 (G1934A) of CYP 2D6 gene the method of PCR-RFLP has been used. Results: An increased risk of BC development in hereditary tainted patients with genotype *4*4 of CYP 2D6 gene compared to the control group has been revealed. The frequency of *1*4 (IM) genotype has been found to be increased in the group of women with a family history of cancer (41.79%). Significant difference between the frequency of *1*1 (ЕМ) and *1*4 (ІМ) genotypes in females with PR-positive and PR-negative tumors in the group of hereditary tainted patients has been registered. Conclusion: In conclusion, our study has revealed an increased risk of BC development in hereditary tainted patients compared to control group with genotype *4*4 (РМ).